The Meaning Of Amānāh In Managing Household Finances Towards Blessing - Latifah, Luluk; Hadi, Abd; Huda, Sholihul; Haqqi, Abdurrahman Raden Aji; Salim, Lutfi Agus (TSAQAFAH, 2024)
Amānāh is all religious duties or encumbrances covering worldly and hereafter matters which are addressed to humans. Without the value of Amānāh social and state life can be damaged, including life in a household. The concept of Amānāh that is built will not be separated from the culture and social influences of one's place of residence. In accordance with the term, the word Amānāh is taken from Islamic grammar and then adapted to the context of Indonesian society and has the meaning of being trustworthy. then the term Amānāh is attached to people who can be trusted. However, this concept is not yet operationally clear. Therefore, it is necessary to understand the meaning of the mandate both conceptually and operationally. All of this will be investigated and discussed later in this research, not only capturing the value of Amānāh from a conceptual point of view but will be explained operationally.The meaning of Amānāh in this study was built with a qualitative phenomenological approach from the main informants as housewives and from experts in various scientific fields related to the value of the Amānāh itself which is associated with household financial management. The various scientific fields are the field of Sharia economics, the field of Islamic religion, the field of psychology and the field of sociology. The results of the study about the meaning of Amānāh is a mandate, a trust, a honesty and proportionality.